Sistem Informasi Donor Darah Berbasis Android Pada Unit Transfusi Darah (UTD) Palang Merah Indonesia (PMI) Kabupaten Bulukumba - Nurul Latifah; Adi Candra; Juniarti Iryani (Journal System Information And Computer, 2024)
This study aims to (1) build an android-based blood donor information system for the PMI Blood Transfusion Unit (UTD) in Bulukumba Regency (2) find out how to display a map of the location and route from the user's position to the destination of the blood donor activity. The method used is the waterfall method, called Waterfall because the stages that are passed must wait for the completion of the previous stage and run sequentially. This development model is linear from the initial stage of system development, namely the planning stage, to the final stage of system development, namely the maintenance stage. The results of this study are: (1) With the Sidonor application, the PMI Blood Transfusion Unit in Bulukumba Regency can disseminate blood stock information, schedules and blood donor locations, besides that in this application, there is a question and answer form that can make it easier for users to communicate with the admin. In designing this blood donor information system using UML (Unifield Modeling language) as the system design and made using the Java programming language and Firebase as the database and testing this system using blackbox testing and the results of this test have run as expected (2) By clicking on the bottom location on the location & schedule menu, the system will direct the user to the location of the blood donor activity with the help of Google Maps, this can make it easier for the user to find the location of the blood donor activity.